2021
DOI: 10.31983/jkg.v8i2.7611
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Consumption of Marine Fish Nanoparticles on the Hardness of Teeth Enamel in Mice (Mus Musculus)

Abstract: Struktur enamel terdiri dari 96 % bahan anorganik, 4% bahan organik, air dan jaringan fibrosa. Ikan laut memiliki banyak kandungan seperti Kalsium, Taurine, Omega 3, PUFAs, Vitamin A, Vitamin D, dan Fluorida yang memiliki fungsi dapat meningkatkan kekerasan enamel gigi. Penelitian ini bertujuan untuk mengetahui pengaruh konsumsi serbuk nanopartikel ikan laut terhadap kekerasan enamel gigi anak mencit (mus musculus).Metode penelitian ini menggunakan jenis penelitian True Experimental dengan rancangan penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…IGF will help move the amelogenin protein secreted by ameloblast cells during the secretory stage. 3,9,16 This study found a significant decrease in the expression of amelogenin with the provision of saltwater fish powder (Figure 1). This is done by Wu et al, 17 and C-terminal brushite-interaction amelogenin with AFM at low concentrations is stated (1-10 nM).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…IGF will help move the amelogenin protein secreted by ameloblast cells during the secretory stage. 3,9,16 This study found a significant decrease in the expression of amelogenin with the provision of saltwater fish powder (Figure 1). This is done by Wu et al, 17 and C-terminal brushite-interaction amelogenin with AFM at low concentrations is stated (1-10 nM).…”
Section: Discussionmentioning
confidence: 75%
“…1 The mineralization phase of primary teeth begins during the fourteenth intrauterine week, and all primary teeth will be fully mineralized after birth. 2,3 Calcium and phosphate comprise around 95% of enamel, making it the most complicated tissue in the human body. One of the proteins that become engaged in the enamel development stage is called amelogenin.…”
Section: Introductionmentioning
confidence: 99%